2019
DOI: 10.2134/agronj2018.03.0201
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Nitrogen Management on No‐Till Maize Production Following Forage Cover Crops

Abstract: Core Ideas Urochloa brizantha as cover crop produced more biomass and nutrient cycling than U. ruziziensis. Nitrogen fertilizer on Urochloa cover crops increased biomass production but limited maize yield. The highest maize yields were obtained when N was applied on day before seeding or under conventional method (N applied at seeding plus sidedressing). All N applied on Urochloa residue prior to maize can be an option, but is risky in regions of high rainfall. Crop residue decomposition is slower in no‐till … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
3
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 52 publications
5
43
3
3
Order By: Relevance
“…The higher biomass yield of palisade grass led to greater N accumulation at termination due to the faster growth and higher NUE of palisade grass. Contrary to the results of the present study, Pacheco et al (2011) and Momesso et al (2019) found similar N accumulation in the two species despite the higher shoot dry matter yield of palisade grass.…”
Section: Effect Of Nitrogen Application On Forage Grassescontrasting
confidence: 99%
See 3 more Smart Citations
“…The higher biomass yield of palisade grass led to greater N accumulation at termination due to the faster growth and higher NUE of palisade grass. Contrary to the results of the present study, Pacheco et al (2011) and Momesso et al (2019) found similar N accumulation in the two species despite the higher shoot dry matter yield of palisade grass.…”
Section: Effect Of Nitrogen Application On Forage Grassescontrasting
confidence: 99%
“…When N fertilizer was applied on palisade grass at 40 and 35 DBS in E1, the forage grass produced approximately 14 Mg ha -1 of shoot dry matter and 200 kg ha -1 of accumulated N. These residues and N accumulation promoted higher shoot dry matter and yields of upland rice compared with the conventional method of N application and the control. In contrast to our findings, a study on the same farm in which all N fertilizer was applied on grasses reported a lower grain yield of subsequent maize compared with the conventional recommended N application at seeding and in the V 4 to V 6 growth stage of maize (Momesso et al 2019). Apparently, the response of the subsequent crop to N fertilization on forage grass is dependent on the crop species and its response to N.…”
Section: Effect Of Nitrogen Application On Forage Grassescontrasting
confidence: 99%
See 2 more Smart Citations
“…En estos sistemas, una estrategia de implementación consiste en el uso de mezclas de fertilizantes con las semillas forrajeras para la aplicación simultánea de los dos insumos durante o después de la siembra del cultivo principal (LIMA et al, 2010). En la segunda aplicación de los fertilizantes nitrogenados representa un momento adecuado para la siembra de brachiarias, disminuyendo el riesgo de competencia entre el cultivo principal y evitando mermas en el rendimiento del grano, o de la biomasa de cultivo principal durante el ensilado u otra forma de alimentación animal (COSTA et al, 2017;OLIVEIRA et al, 2018;MOMESSO et al, 2019).…”
unclassified